(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Nature-based learning makes learners connect to the natural environment in all subjects to have direct experiences in both human-built and natural environment in their community, time to only be in nature, to play, and to become naturally curious to powerfully stimulate their sense of wonder and discovery, using their critical thinking to make decisions about and act for the environment. This study was designed to assess the level of development of the learners of San Julian Integrated School Kindergarten pupils along with the Cognitive and Affective Domains, which led the researcher to design a Nature-Based Learning Teachers’ Guide. This study used the quasi-experimental design of research where the researcher employed the Cognitive and socio-emotional domain of the Early Childhood Care and Development (ECCD) checklist to the 25 kindergarten pupils enrolled this School Year 2019-2020 as rated by the teacher. The researcher utilized weighted means for the level of development of the domains of the participants and t-test on the level of validity of the teacher’s guide. The findings showed that before the implementation of the teachers’ guide, the domains were developed moderately; after the implementation, the domains were developed highly. It was noted that there is a difference between the domains before and after the implementation of the teachers’ guide. It is recommended that the formulated Nature-Based Learning Teacher’s Guide be utilized in kindergarten. As an output, the researcher made a Nature-Based Learning Model for teachers to help in the development of the child holistically.